Incorporation of metal (silver, copper, iron) chalcogenides (oxide, selenide) nanoparticles into poly(methyl methacrylate) fibers for their antibacterial activity - Sibokoza, Simon Bonginkosi (Vaal University of Technology, 2020)
Nanoscience receives a lot of attention in the 21 century and is one of the most advancing technology in our days. It provides many new and advanced technological opportunities. This field involves many disciplines which include chemical, physical, and biological related fields. The advancement of nanoscience makes life to be better and bring about new inventions which can solve many problems in our day to day life. Although there are reservations about the use of these materials in other fields. Some researchers believe that these materials can be a problem to the environment and humanity at large. Therefore, more research needs to be done to fully understand these materials. Polymer science is another field that has been advancing every day. Many problems in our lives require material which have properties from nanomaterials and polymers. The combination of these technologies can leads to new materials which have many possibilities in solving most problems. Some researchers have taken advantage of these two powerful fields and merge them. There has been a lot of work done that involves combination of nanotechnology and polymer science. The current project is an initiative to manufacture nanofibers. These fibers are prepared using polymer solution mixed with metal oxide and metal selenide nanomaterials. The polymer solution is incorporated with nanoparticles and electrospunned to make nanofibers. The electrospinning afford the material prepared to be at nanoscale. The fact that the material formed is at nanoscale opens many possibilities to be used in various fields. The study is about fabrication of polymer nanofibers embedded with metal chalcogenide nanoparticles. The metal oxide and metal selenide nanoparticles were prepared using complexes. These complexes contain both the metal and the chalcogenide of interest. The complexes are prepared from oxygen-based (urea), and selenium-based (diphenyldiselenide) ligands. The urea complexes co-ordinates with metal using oxygen for iron, however in silver complexes both nitrogen and oxygen are used. These complexes allow easy control of reaction parameters, and thermal decomposes to form metal oxide, metal selenide, and metal. The complexes are very stable and decomposes at about 200 °C. These compounds are thermal decomposed to form metal chalcogenides, and metal nanoparticles. The complexes are characterized with FTIR, TGA, and elemental analysis. The metal chalcoginedes (copper oxide, iron oxide, silver oxide, copper selenide, iron selenide, and silver selenide) nanoparticles were prepared using thermal decomposition of a single source (complexes or metal salts). The prepared chalcogenides nanoparticles have good absorption and emission properties consistent with small sizes. These nanoparticles are composed of various phased and stoichiometry. Some metal chalcogenides have a mixture of stoichiometry and phase. The metal chalcogenides nanoparticles are dominated by spheres, and other shapes such as rods. These metal chalcogenides have a particles size in the range of 1-36 nm. The metal chalcogenides nanoparticles were tested against bacteria and fungi. These nanoparticles show highest activity in gram positive compared to gram negative bacteria. Metal oxide nanoparticles show the highest activity compared to metal selenide. All the metal chalcogenides show the highest against fungi. The nanoparticles are able to inhibit the fungi at lowest concentration. The nanoparticles are characterized with various instruments which includes UV-Vis, PL, XRD, and TEM. Nanofibers of poly(methyl methacrylate) (PMMA) incorporated with metal selenide and metal oxide nanoparticles were prepared by electrospinning. The nanofibers incorporated with metal chalcogenide are more thermal stable than PMMA nanofibers. Therefore, incorporation of metal chalcogenides nanoparticles leads to more thermal stability nanofibers. The PMMA are coordinated to the metal oxide and metal selenide through carbonyl oxygen atom. The PMMA incorporated with metal oxide and metal selenide leads to the formation of nanofibers with uneven surface with a diameter in the range of 30 to 200 nm. The prepared fibers are characterized using FTIR, TGA, SEM.
D. Tech. (Partial Fulfillment) (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Nanoscience; Polymer science; Nanotechnology; Nanofibers; Polymer nanofibers; Metal chalcogenide nanoparticles; Oxide; Selenide; Antibacterial activity; Poly (methyl metacrylate); Dissertations, Academic -- South Africa.; Nanoparticles.; Polymers.; Nanocomposites (Materials).; Nanostructured materials.